Античний світ в художній рецепції О. Ольжича - Шацький, І.В. (Культура народов Причерноморья, 2013)
У статті розглядаються проблеми, пов’язані з осмисленням та інтерпретацією
історіософських мотивів у творчості О. Ольжича. З’ясовуються причини звернення до античних
мотивів. Досліджується суб'єктна сфера лірики О. Ольжича з погляду найбільше виражених у ній
категорій ліричного героя, його характеру, їх еволюції, взаємозв’язку з образом власне автора.
Осмислюються особливості ідіостилю Ольжича-поета, його світовідчуття; висвітлюється
історичний, літературний та філософський контексти творчості. В статье рассматриваются проблемы, связанные с осмыслением и интерпретацией
историософских мотивов в творчестве О. Ольжича. Рассматриваются причины обращения к
античным мотивам. Исследуется субъектная сфера лирики О. Ольжича с точки зрения наиболее
выраженных в ней категорий лирического героя, его характера, их эволюции, взаимосвязи с образом
собственно автора. Осмысливаются особенности идиостиля Ольжича-поэта, его мироощущение,
освещается исторический, литературный, философский контексты творчества. This article is devoted to the analysis of the antique themes of O. Olzhych poetry in particular to
studying the character and the evolution of the lyrical hero in O. Olzhych poetry.
The subjective organization of O. Olzhich’s lyrics and lyrical epos from the point of view of its the most
expressed categories of lyrical hero, its character, their evolution, interconnection with the image of the author
itself is analyzed.
Forms and ways of the textual realization of the given categories, the artistic realization of “the aesthetics of
action”, the special features of O. Olzhich’s idiostyle, his attitude are revealed; historical, literary and
philosophical contexts of his works are interpreted.
In his works O. Olzhich took great attention to revealing of the historiosophic possibilities of Ukrainian poetry.
He was interested not only in traditional cossac or Kyiv Russ motives but he was also absorbed in the
considerably distant past, which he knew being an archeologist. He took an interest the military democracy
period, that was the decisive factor in formation and developing of the heroic ethnos. It brought the initiative of
the creative person, the emancipation of the individual origin in spite of the still ruling overpersonality in the
primitive society. The heroic spirit which arose in such conditions excited Olzhich’s exceptional interest first of
all because of revealing the substancial value of human individuality and society as equal notions which were
protected by the Prague school aesthetics.
The past and the present are indissoluble for Olzhich lyrical hero. And if the author himself however lives “here
and now”, his lyrical hero lives in different time measures, his memory moves easily through the epochs,
wending his way from the past to the present and foreseeing the future.
For expressing the character of the lyrical hero the author uses the vast palette of means. Most frequently he
reveals himself via his behaviour both external (deeds, manners, language) and internal (thoughts, dreams,
experience, states). The direct characterizing is often used.